Implementasi Model Pembelajaran Project Based Learning (PJBL) dalam Meningkatkatkan Kreativitas Siswa pada Mata Pelajaran Bahasa Indonesia Kelas IV SD IT Al Fikri Islamic Green School - Rahma Tilla Indah; Salman Salman; Radhiyatul Fithri (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research aims to find out how the implementation of the Project Based Learning (PJBL) learning model increases student creativity in Indonesian language subjects for class IV SD IT Al Fikri Islamic Green School. This research uses descriptive qualitative research methods which were carried out at SD IT Al Fikri Islamic Green School for the 2023/2024 academic year. The research was carried out through the opening stages of learning, planning projects and determining groups, preparing activity schedules, supervising the progress of projects and assessments. The research subjects were class IV of SD IT Al Fikri Islamic Green School, totaling 28 people. The research showed that teachers planned project based learning according to standards. module process Data was collected using sheets, knowledge tests, observation of student activities, documentation and interviews. The data collected was analyzed using qualitative descriptive analysis.The results of the research show that the Project Based Learning (PJBL) learning model can increase the creativity of fourth grade students at SD IT Al Fikri Islamic Green School in learning Indonesian as evidenced by the increase in student scores which are better than before.